2020
DOI: 10.3906/sag-1908-93
|View full text |Cite
|
Sign up to set email alerts
|

Could HIF-1α be a novel biomarker for the clinical course and treatment of pulmonary embolism?

Abstract: Background/aim: Pulmonary embolism (PE) is associated with high morbidity and mortality rates if not diagnosed and treated rapidly. The aim of our study was to investigate the relationship between levels of hypoxia-induced factor-1 alpha (HIF-1α) and clinical course and prognosis in patients with intermediate low-risk, intermediate high-risk, and high-risk PE. Materials and methods: The study included 240 subjects in 4 groups: a healthy control group (n = 60, mean age = 60 ± 15.2, female/male = 30/30), interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…3 Right ventricular dilatation results in the release of certain cytokines to ensure oxygenation, neovascularization, and rapid thrombus organization. 4 The most important of these cytokines is vascular endothelial growth factor (VEGF). 5 VEGF causes endothelial proliferation and neovascularization, and prevents reperfusion injury by increasing glutathione peroxidase activity.…”
mentioning
confidence: 99%
“…3 Right ventricular dilatation results in the release of certain cytokines to ensure oxygenation, neovascularization, and rapid thrombus organization. 4 The most important of these cytokines is vascular endothelial growth factor (VEGF). 5 VEGF causes endothelial proliferation and neovascularization, and prevents reperfusion injury by increasing glutathione peroxidase activity.…”
mentioning
confidence: 99%
“…Many studies have shown the application of HIF-1a in diagnosing diseases with tissue hypoxia. Kergert et al 20 found that HIF-1a plays a vital role as a biomarker in the early diagnosis and disease risk stratification of pulmonary embolism. Other studies have also…”
Section: Discussionmentioning
confidence: 99%
“…Kergert et al. 20 found that HIF-1α plays a vital role as a biomarker in the early diagnosis and disease risk stratification of pulmonary embolism. Other studies have also shown that HIF-1α may be a helpful indicator for the early diagnosis of acute decompensated heart failure or renal vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…PTE is one of the major emergencies for which morbidity and mortality rates are declining due to advances in early diagnosis and treatment [8]. In treatment, the duration of secondary prophylaxis varies based on the risk factors present [9][10][11]. It was reported that 81% of 69 PTE patients followed up with CT angiography had complete resolution after 4 weeks [12].…”
Section: Discussionmentioning
confidence: 99%